(untitled) (Tribhuvan University Law Journal, 2025)
Visiting Nepal as case study, this article attempts to address the issues of transitional justice related law making in the Nepal and recent progress. While the armed conflicts resulting in the decades of violent atmosphere have long ended, memories of the mass atrocity crimes that occurred during the 1990s and early 2000s continue to cast a long shadow over the peace process. Its post-conflict achievements have been extraordinary including, inter alia, promulgation of new constitution, but on the dark side of the transition there are more problematic realities. Little of what the Comprehensive Peace Accord (CPA) envisioned for Nepal has come to fruition in the nineteen years since it was signed, and the government made limited progress securing accountability or redress for the violations committed during the conflict. Therefore, the Article argues that transitional justice cannot succeed in Nepal without a credible, robust, proper and principled justice mechanism capable of ensuring accountability for victims of past abuses and end to the peace process at large. Article seeks for the strong commitment on the part of the State and political leaders to the honorable and successful exit from the transitional justice process for which formulation of the effective law is the first steps.